A biofísica e os livros didáticos do PNLD: uma relação interdisciplinar nos livros de física - Kugler, Derick de Almeida Fontoura (2017)
This research presents the results of an investigation that has the goal to analyze how Biophysics, as an interdisciplinary field, can be found in the PNLD Physics Didactic Textbooks. The relationships between disciplines and their classifications, established by Heckhausen (1972) and Japiassu (1976), were used to locate each area that Biophysics contemplates, and their level of interdisciplinarity with Physics. The studied universe was the textbooks of 2015, more recent at the time of writing, which are easier to find and better reflect the current panorama of physics teaching in Brazil at the moment. The analysis of the data was done using the Content Analysis, proposed by Bardin (2009). During the analysis, the data were separated into two groups, one of which was about the main text, boxes and extra sections of the textbooks, and the other looked at the exercises and activities. Once the information was collected, a recurrence table was created to aid in classification using a Likert scale. The results obtained with this work demonstrate that each area of Biophysics, such as Biotermology, Bioacoustics and Bio-optics present different types of interdisciplinarity, both question and main text. The encyclopedic use of information in order to motivate the discussions about a content of physics, or to end one of the chapters, misleading the impression that Biophysics is nothing more than an application of Physics in Biology.